I.viii.1 Minutes - Labour Party (Ireland) (1995)
Minutes and supporting documentation of five meetings of the Policy Committee which took place between 11 Jul 2001 - 8 Sept 2004. Also includes mission statement of the policy development commission, dated 1995. (18 pp)
Minutes and supporting documentation of four meetings of the Policy Committee which took place between 19 Jan 2005 – 5 Dec 2005. Also includes notice of two meetings, dated 16 Feb 2005 and 21 Mar 2005. (73pp)